Rapid diagnosis of seasonal influenza virus and cohorting of hospitalized patients on an influenza ward: a prospective analysis of outcomes. Issue 3 (July 2020) - O'Kelly, B.; Conway, A.; McNally, C.; McConkey, S.; Kelly, A.; de Barra, E.
Summary: Background: The influenza season of 2017/2018 was burdensome in comparison with previous years. Management of patients with seasonal influenza is poorly described. Aim: To assess the impact of managing patients with influenza on a dedicated influenza ward on antimicrobial use and duration, and length of stay (LOS). Methods: A prospective cohort study was performed from 1 st January to 28 th February 2018. Patients diagnosed with influenza in the emergency department (ED) were cohorted under infectious disease (ID) or general internal medicine (GIM) services on a 35-bed influenza ward. At times of maximum capacity, some patients were managed on other wards by other services. Findings: Ninety-one patients were admitted to the influenza ward from the ED (64 ID, 27 GIM); of these, 38 patients had influenza A. Patients managed by the ID service were generally switched to oral antibiotics sooner than patients managed by the GIM service (median 3 vs 5 days; P =0.049). Antibiotic duration was shorter for patients managed by the ID service compared with patients managed by the GIM service (median 7 vs 9 days; P =0.016). LOS was shorter for patients managed by the ID service on the influenza ward compared with patients with influenza on non-influenza wards (median 5 vs 9 days; P =0.007). No significant difference in LOS was seen between patients on the influenza ward managed by the ID and GIM services (median 5 vs 7 days; P =0.30). Conclusion: Patients with influenza managed by the ID service on the influenza ward had a shorter duration of intravenous and total antimicrobial use compared with patients managed by the GIM service, and had reduced LOS compared with patients with influenza on non-influenza wards.